Perencanaan Pembaharuan Jaringan LTE FDD (Frequency Division Duplex) Pada Frekuensi 900 MHZ Di Kabupaten Bengkalis - Erma Yuli Clara Saragih; Linna Oktavianasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Long Term Evolution (LTE) is a technology that became a trend recently. Bengkalis Regency is area has not yet applied LTE technology optimally and even there is no positive change. This condition be basis for this paper. This paper uses design and simulation of Frequency Division Duplex (FDD) 900 MHz through Atoll Software, based on research that has been done previously in several other areas. FDD design is done with four scenarios that results will be compared, to see the best parameter in that area. There was used frequency 900 Mhz with bandwith 5 MHz and 10 MHz, 1800 MHz with bandwith 5 MHz and 10 MHz. That compared in that scenario are signal level, uplink and downlink CINR analysis, Service Area Analysis downlink and uplink and Monte Carlo analysis. The best scenario is a scenario with a frequency 900 MHz, bandwidth 10 MHz and required number of cells at least 137 eNodeB. Signal coverage level is capable of reaching ≤ -65 dBm, while the downlink CINR signal level ≥ 2,479 dB and ≥ 17 dB for uplink CINR signal level. While for Monte Carlo simulation can reach connected user is 81,4% which is connected, for uplink and downlink throughput reaching ≥ 1 Mbps.Keywords: LTE, Atoll, FDD, 900MHz